Transmission Strategy Design in Cognitive Radio Systems With Primary ARQ Control and QoS Provisioning - Seifali Harsini, Jalil; Zorzi, Michele (IEEE transactions on communications, 2014)
In this paper, we consider an underlay cognitive radio paradigm with a primary packet system which implements automatic repeat request (ARQ)-based error control. We propose cognitive transmission strategies which provision for minimum primary quality of service (QoS) requirements. The proposed strategies take advantage of opportunities that arise during ARQ retransmissions of the primary system at the link layer, and adapt channel fading variations by employing adaptive modulation and coding (AMC) and power control at the physical layer. In this cross-layer formulation, the cognitive throughput is optimized subject to 1) a packet-loss-rate (PLR) constraint on the cognitive link, and 2) a minimum required throughput and a PLR constraint on the primary link. We first derive analytical expressions for the link-layer throughput of the cognitive link defined in terms of the data rate successfully received at the receiver side. Next, we present optimized AMC and power control schemes for the cognitive transmitter. Numerical results show significant improvement in terms of the cognitive throughput and PLR performance. Namely, when the cognitive transmitter employs both power and rate control the throughput-maximizing strategy is determined based on a tradeoff between the primary PLR and delay (in terms of the number of retransmission rounds) QoS metrics.